Loksado Community Participation in Improving Nature Tourism in Loksado - Dotrimensi Dotrimensi; Yenti Astiar; Apriliani Apriliani; Rensianae Rensianae; Ninin Aderini (CV. Rayyan Dwi Bharata, 2023)
Tourism as a leading sector is expected to be one of the engines of economic growth, this can be seen from the contribution of tourism to economic growth and creation of job opportunities, increasing people's incomes and equitable development. Loksado District, South Hulu Sungai Regency, South Kalimantan Province as a natural tourist spot that has beauty and is an attraction for South Kalimantan and has become a sector of excellence in Loksado. In this study the authors used the observational interview research method in seeking information and data about the topics discussed. This study aims to find out how the participation of the Loksado community in improving nature tourism in Loksado. The participation or social participation of the people in Loksado is very high, especially in terms of advancing the districts in Loksado or the community itself. As is the case in the development of tourist objects in Loksado, social forms and local community participation, namely, can play an active role in developing tourism products and services in Loksado. The local government and the community still need to increase cooperation and participation in tourism in Loksado. The local government and the tourism agency must socialize with the relevant Loksado community in developing and increasing tourism in Loksado. One thing that is also necessary is to add training from the local government, in order to add insight, speaking skills and foreign language skills to the community.